A Model to Reduce Machine Changeover Time and Improve Production Efficiency in an Automotive Manufacturing Organisation - Niekurzak, Mariusz; Lewicki, Wojciech; Coban, Hasan Huseyin; Bera, Milena (Sustainability, 2023)
One of the key postulates of the modern automotive industry is the increase in production efficiency while minimizing costs. In the opinion of experts from the automotive industry, meeting this condition may be the first stage on the way to preventing waste generation and implementing a circular economy model. The article presents a case study of issues related to the lean manufacturing methodology in terms of the impact of shortening the changeover time of the assembly line on the overall production efficiency. The presented considerations focus on the optimization of the production process using the SMED (Single Minute Exchange of Die) technique of a selected spare part. From the point of view of the Lean Manufacturing concept, the main goal of the SMED technique is to increase the flexibility of responding to changing customer needs by shortening the changeover times and faster responses to changing orders. The article describes the stages of implementing the SMED method and its impact on the increase in the OEE (Overall Equipment Efficiency) index, which allows for the percentage recognition of the degree of machine park utilization, which is one of the key factors for assessing energy efficiency. In addition, the benefits that have been achieved by using this method in terms of time and economy have been presented. The theoretical aspects related to the method used were supplemented with its practical implementation in order to improve the changeovers in a manufacturing company in the automotive industry. Based on the obtained test results, an analysis of the effectiveness of the measures taken to reduce the changeover time was carried out. The use of the SMED methodology contributed to a significant reduction in changeover time—by as much as 291.4 s. The burden on operators was significantly reduced—the total time and number of operations performed by them (both internal and external) was reduced. Operator paths have also been shortened using simple procedures such as changing the layout of the lines and modifying the changeover tool trolleys and tool locking system at the stations. The presented research may be helpful in answering the question whether the implementation of the SMED idea may be the key to effective resource management and, at a later stage, to the implementation of the circular economy model. In addition, the research results can find their practical application among both manufacturers of spare parts and the vehicles themselves, considering introducing process changes on their production lines in order to increase production efficiency and implementing the idea of industrial sustainability.